Tinjauan Kimia Medisinal dalam Pengembangan Obat Berbasis Flavonoid: Studi Literatur - Saeful Amin; Wulandari, Ratna (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Flavonoids are natural polyphenols that are abundantly found in a wide variety of fruits, vegetables, seeds, and medicinal plants, and are known for their wide-ranging antioxidant, anticancer, anti-inflammatory, and antidiabetic effects. This comprehensive review outlines the important role of medicinal chemistry in the development of flavonoid-based therapeutics, with a particular focus on classification, structure activity relationships (SAR), mechanisms of action, and various strategies to improve bioavailability. Literature from PubMed, Scopus, and Google Scholar indicates that structural features such as hydroxyl group number and position, the C2=C3 double bond, and modifications like methylation, glycosylation, or prenylation strongly influence biological activity and pharmacokinetics. Clinical use is limited by poor solubility, rapid metabolism, and low stability. Chemical modification and advanced delivery systems including liposomes, nanoparticles, nanocrystals, micelles, and natural carriers can enhance solubility and plasma concentration. Combining medicinal chemistry with modern formulation technologies may enable flavonoids to become safe and effective therapeutic agents.